2000
DOI: 10.1080/10473289.2000.10464211
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Effects of Sugar Cane Plantation Burning on Daily Counts of Inhalation Therapy

Abstract: This study was designed to evaluate the association between sugar cane plantation burning and hospital visits in Araraquara in the state of São Paulo, Brazil. From June 1 to August 31, 1995, the daily number of visits of patients who needed inhalation therapy in one of the main hospitals of the city was recorded and used as health impairment estimation. Sedimentation of particle mass (the amount of particles deposited on four containers filled with water) was measured daily. The association between the weight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
55
1
23

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(79 citation statements)
references
References 9 publications
0
55
1
23
Order By: Relevance
“…But there are few studies conducted in cities located in regions producing sugarcane correlating the effects of straw burning and its impact on population health. 21,22 In the present study, it was found that the distribution of air pollutants has seasonal aspects, and the average levels of these pollutants were below those observed by Braga et al 9 and Bakonyi et al 8 , although higher than those found by Souza et al 19 in a study carried out in Campo Grande, MS, and by Moura et al 20 in Rio de Janeiro. This result is quite interesting since Araraquara is a medium-sized city located in the state of São Paulo.…”
Section: Discussioncontrasting
confidence: 51%
“…But there are few studies conducted in cities located in regions producing sugarcane correlating the effects of straw burning and its impact on population health. 21,22 In the present study, it was found that the distribution of air pollutants has seasonal aspects, and the average levels of these pollutants were below those observed by Braga et al 9 and Bakonyi et al 8 , although higher than those found by Souza et al 19 in a study carried out in Campo Grande, MS, and by Moura et al 20 in Rio de Janeiro. This result is quite interesting since Araraquara is a medium-sized city located in the state of São Paulo.…”
Section: Discussioncontrasting
confidence: 51%
“…Ninety articles (66%) deal with the adverse respiratory effects of air pollution of which 54 (60%) were selected 21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,…”
Section: Published Articlesmentioning
confidence: 99%
“…Where sugarcane is grown and processed, the population has suffered from constant burning in the fields 27 , which increases the release of air pollutants, responsible for various health problems 41,42 . Ribeirão Preto has been heavily affected by this problem in recent decades, not only due to burning in sugarcane fields, but also by fires set by the residents themselves, who believe that burning fallen leaves and branches and the weeds growing on and around their lots, or even household garbage, will solve the problem of accumulated waste around their homes.…”
Section: Discussionmentioning
confidence: 99%